2012
DOI: 10.1161/circinterventions.112.971390
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Transluminal Pulmonary Angioplasty for the Treatment of Chronic Thromboembolic Pulmonary Hypertension

Abstract: C hronic thromboembolic pulmonary hypertension (CTEPH) is defined as a progressive disease of increasing pulmonary vascular resistance because of chronic thromboembolism in the pulmonary arteries that leads to pulmonary hypertension (PH), right-sided heart failure, and a grave prognosis. [1][2][3][4][5][6][7][8][9] Several studies have demonstrated the efficacy of medical therapies using anticoagulation and pulmonary vasodilators, including several newly developed agents. 1,10,11 The most powerful conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
209
1
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(253 citation statements)
references
References 20 publications
7
209
1
18
Order By: Relevance
“…5,14,15) Although the mechanism of lung injury has been considered to be reperfusion injury by cytokine release or pressure overload, recent reports have demonstrated that mechanical damage by the guide wire or balloon is also one of the causes. 5,9) However, in the present study, lung injury did not depend on the increasing frequency of BPA sessions or treated vessels, technique of the operator, balloon size, pressure of the balloon inflation, or guide wires.…”
Section: Discussionmentioning
confidence: 99%
“…5,14,15) Although the mechanism of lung injury has been considered to be reperfusion injury by cytokine release or pressure overload, recent reports have demonstrated that mechanical damage by the guide wire or balloon is also one of the causes. 5,9) However, in the present study, lung injury did not depend on the increasing frequency of BPA sessions or treated vessels, technique of the operator, balloon size, pressure of the balloon inflation, or guide wires.…”
Section: Discussionmentioning
confidence: 99%
“…Both reports mentioned specific complications related to this procedure. Meanwhile, several Japanese centres gained their own experience in BPA using slightly different methodologies and claimed reduced complication rates while maintaining high efficacy [7][8][9][10][11][12][13][14]. We started to perform BPA in non-operable CTEPH patients in 2013 [15,16], motivated by their expected poor survival compared with those offered surgical PEA [2].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary endarterectomy (PEA) is a gold standard therapy7, 8; however, PEA for organized thrombus located peripherally in subsegmental pulmonary arteries was less effective and had a high perioperative mortality rate 7, 9. Presently, balloon pulmonary angioplasty (BPA) can be recommended as an established treatment for nonoperable CTEPH patients 10, 11, 12, 13, 14, 15, 16…”
mentioning
confidence: 99%